Re-reading Niebuhr's The Children of Light and the Children of Darkness: The crisis of democracy in an interdependent world then and now. (June 2021) - Ashworth, Lucian M
Reinhold Niebuhr's The Children of Light and the Children of Darkness is one of the key English-language texts in the post-war settlement literature of the early 1940s. This article analyses the book on three interconnected levels: the nature of the argument made by Niebuhr in the book, its place in the broader post-war settlement literature of the early 1940s, and its relevance to the current problems of right-wing populism and the climate crisis. While the main theme of the book is the necessity and impossibility of democracy, it shares with the work of Isaiah Bowman and David Mitrany a concern for the tension between the state and interdependence. The deepening of this tension since has helped keep Niebuhr relevant, although his initial distinction between the children of light and the children of darkness has been complicated by both populism and the climate crisis.